Construção e caracterização de uma enzima quimérica obtida pela fusão gênica endoglucanase-xilanase de Trichoderma harzianum - Santiago, Adelita Carolina (Universidade Federal de São Carlos, 2013)
The sugarcane bagasse is a lignocellulosic material that can be converted into ethanol by action of cellulases and xylanases. These enzymes act synergistically to convert cellulose and hemicellulose into glucose. In order to obtain an enzyme that can perform dual function, a chimeric enzyme cellulase-xylanase denominated ThEg3Xyn3, was constructed by gene fusion in our laboratory. The fusion was performed by binding the C-terminus of an endoglucanase from Trichoderma harzianum to the N-terminus of a xylanase of the same fungus, separated by a linker. The chimeric enzyme was recombinantly produced in Pichia pastoris and purified for kinetic and biochemical characterization. The chimera demonstrated activity of both enzymes with maximum activity at 38 °C and pH 6.0, under these conditions, cellulolytic and xylanolytic activity was greater than of the parental enzymes. The results demonstrate that the chimeric enzyme can be efficient in hydrolysis of the biomass and satisfactory for the production of ethanol by the process of simultaneous saccharification and fermentation.
Keywords: Biologia molecular; Bioetanol; Enzimas; Fusão gênica; Trichoderma harzianum; Quimera; Chimera; Fusion; Ethanol; Trichoderma harzianum; CIENCIAS BIOLOGICAS::GENETICA